Performance evaluation of a QoS‐aware error control scheme for multiple‐WBAN environment. (June 2017) - Takabayashi, Kento; Karvonen, Heikki; Paso, Tuomas; Tanaka, Hirokazu; Sugimoto, Chika; Kohno, Ryuji
Abstract : This paper presents a comprehensive performance evaluation of an error control scheme using decomposable codes while satisfying quality of service (QoS) requirements in a multiple‐wireless body area network (WBAN) environment. Our QoS control scheme comprises a multiplexing layer and decomposable error control coding used to adapt the communication parameters and satisfy the different performance requirements of different types of WBAN data traffic. Using mathematical analysis and simulations, it has been shown in previous studies that this method has a better residual bit error ratio (RBER) and throughput performance than that of an IEEE 802.15.6‐based solution. The energy efficiency of the proposed method was recently evaluated for an additive white Gaussian noise case. In this work, this performance evaluation IS complemented by simulating the RBER performance under a defined worst case scenario. The energy efficiency is compared with that of the IEEE 802.15.6 solution using a realistic WBAN channel model and accounting for the interference from neighboring WBANs. Results from the previous studies and the new results are given to provide a complete description of the performance of our method. The results demonstrate that an error control scheme based on decomposable codes satisfies the QoS requirements of different data types and provides a more flexible and energy efficient QoS control than that of the IEEE 802.15.6 solution. The scheme is also shown to guarantee communication performance in the worst case scenario, whereas the IEEE 802.15.6 solution fails to do so. © 2017 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.